FREQUENCY MIGRATION CHALLENGES AND STRATEGIC DECISIONS-MAKING IN BROADBAND WIRELESS ACCESS NETWORKS - Sulaeman, Maman
The strategic migration of PT. XYZ's telecommunications network from the 3.3 GHz to the 10 GHz band represents a significant endeavor to capitalize on enhanced bandwidth and service quality while aligning with regulatory standards for sustained growth in a competitive landscape. This thesis meticulously examines the multifaceted aspects of this migration, employing a SWOT analysis, Qualitative Data Analysis, and the Analytical Hierarchy Process (AHP) to discern the optimal pathway forward.